Efecto de la ubicación y diámetro de la rama en tres genotipos promisorios de Myrciaria dubia (H.B.K.) "camu camu" para propagación vegetativa por acodo aéreo - Liao Torres, Jiang Oliver (2012)
[EN] The objective of this study was to evaluate the effect of the location and diameter of the branch in three genotypes of camu camu using the technique of air layering on rooting and sprouting. The mother plants were bent and then rooted branches were transplanted following the design of randomized complete block with three replications. At 3 months after transplantation was the assessment of the variables, finding the best values for the number of roots to the middle third, thick diameter, Genotype MD-015 and the upper, thick diameter, Genotype MD-015 with 28.67 and 28.33 roots, respectively, in the variable length of the upper third roots, thick diameter, Genotype MD-015 showed the best results with 15.27 cm. Regarding the number of outbreaks upper, thick diameter, Genotype MD-014 and the upper, thick diameter, Genotype MD-015 achieved the best results with 13.00 and 12.67 outbreaks, respectively, in the length of shoots, the best treatment was the upper, thick diameter, Genotype MD-015 with 30.73 cm, and finally in the variable number of leaves / shoot highlights the upper, thick diameter, Genotype MD-014 and the upper, thick diameter, Genotype MD-015 with 15.10 leaves per shoot and 14.83, respectively. The results allowed identifying the upper, thick diameter, Genotype MD-015 as the best in terms of rooting and sprouting capacity. -------- [ES] El objetivo del presente trabajo fue evaluar el efecto de la ubicación y diámetro de la rama en tres genotipos promisorios de camu camu utilizando la técnica del acodo aéreo sobre el enraizamiento y brotación. Las plantas madres fueron acodadas, posteriormente las ramas enraizadas se trasplantaron siguiendo el diseño de Bloques Completos al Azar, con tres repeticiones. A los 3 meses del trasplante se realizó la evaluación de las variables, encontrando los mejores promedios para el Número de raíces al Tercio medio, Diámetro grueso, Genotipo MD-015 y al Tercio superior, Diámetro grueso, Genotipo MD-015 con 28.67 y 28.33 raíces, respectivamente; en la variable Longitud de raíces el Tercio superior, Diámetro grueso, Genotipo MD-015 mostró los mejores resultados con 15.27 cm. Con respecto al Número de brotes el Tercio Superior, Diámetro Grueso, Genotipo MD-014 y el Tercio superior, Diámetro grueso, Genotipo MD-015 alcanzaron los mejores resultados con 13.00 y 12.67 brotes, respectivamente; en la Longitud de brotes, el mejor tratamiento fue el Tercio superior, Diámetro grueso, Genotipo MD-015 con 30.73 cm; finalmente en la variable Número de hojas/brote sobresalieron el Tercio superior, Diámetro grueso, Genotipo MD-014 y Tercio superior, Diámetro grueso, Genotipo MD-015 con 15.10 y 14.83 hojas por brote, respectivamente. Los resultados permitieron identificar al Tercio superior, Diámetro grueso, Genotipo MD-015 como los mejores en cuanto a la capacidad de enraizamiento y brotación.